Analysis of Opportunistic Behavior, Monitoring Mechanisms and Financial Distress on Earnings Management: Evidence from Indonesia - Dian Agustina; Nur Anita (Universitas Ahmad Dahlan, 2022)
This study aims to examine the relationship between opportunistic behavior, monitoring mechanisms, and financial distress on earnings management. The population of this study is 796 companies listed in the Indonesia Stock Exchange year 2015-2019. Fourty three sample companies were selected using purposive sampling method, resulting 215 firm-year observation data. Using ordinary least square (OLS) regression as the main data analysis, the study observed that monitoring mechanism variable proxied by leverage has a positive effect on earnings management. However, there is no correlation between opportunistic behavior proxied by free cash flow and profitability as well as financial distress proxied by Altman Z-Score on earnings management. A robustness test using additional data of the samples companies during the COVID-19 pandemic was carried out. The test provides evidence that the results of this study's are robust. This study contributes empirically to the literature on the relationship between opportunistic behavior using free cash flow and profitability proxies, monitoring mechanisms using leverage, financial distress, and earnings management. It also provides valuable information for stakeholders to observe the quality of firm’s financial statements.